If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(10x + 1 * 4) = 0 Multiply 1 * 4 -5(10x + 4) = 0 Reorder the terms: -5(4 + 10x) = 0 (4 * -5 + 10x * -5) = 0 (-20 + -50x) = 0 Solving -20 + -50x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -50x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -50x = 0 + 20 -50x = 0 + 20 Combine like terms: 0 + 20 = 20 -50x = 20 Divide each side by '-50'. x = -0.4 Simplifying x = -0.4
| (2lnx)(2x)= | | -1-5[4+2(c-3)]=2(c+1) | | 63-3x=33x+17 | | 6x-17+4x-12+2x+5=180 | | 1/4*1/3 | | 75.00+25h=40h | | 4+2[4-(3+y)]=-2(y-1)-4+y | | x^3-4x^2+8x-32=0 | | abs(3x-4)=6 | | 4Q+7=-12 | | (3m-6/2)5 | | 220=2x-12c | | (5x-3)+(6x-17)=90 | | 1/2x+1/6x=4 | | 2-5(4-3x)=2(4-x)-8x | | x^3-3x^2+3p-0.95=0 | | 6/7(14z-7)=0 | | (5x-3)+(6x-17)=180 | | 48+6y=0 | | 12z+6-2z=-5z+3(5z+3) | | -12-(-9)/(-3) | | x+4/11=x-2/9 | | 13x^2-8y-9=0 | | -2(15y-2)+30y=4 | | 6z+2(z+3)=2(4z+3) | | 6x-7y=-49 | | v/3+10=15 | | 5b-6=5(b-14) | | 5w-8=52 | | c^2=-35-12c | | -1/2x+3/11=15/22 | | .07(3y+5)=.2(y-5) |